The impact of bilingual schools on children's language development at Shining Little Star Kindergarten Tegal in 2023 - Ines Setiana (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2023)
The learning process on the school that applies bilingual school by using two languages such as English and Bahasa Indonesia as instruction language on the learning activity. By using two languages at the same time, sometimes give pro and contra effect on children’s language development. One of the schools that apply the concept of bilingual school is Shining Little Star Kindergarten Tegal. This research tries to analyze the effect of using two languages on children’s language development and to find out the obstacle experienced by the teachers in implementing bilingual school. The purpose of the research is to find out the implementing of bilingual school give an impact or not for the children’s language development and the obstacle experienced by the teachers. This research used descriptive qualitative method. However the researcher used direct observation, documentation, and interview with teachers and parents as a technic of data collection. The result of this research is shown that the use of bilingual school does not give negative effect to the children’s language development. Moreover, the teachers also did not find an obstacle when implementing two languages because the human resources of the Shining Little Star Kindergarten are competent.